Case reports of portal vein thrombosis and bile duct stenosis after stereotactic body radiation therapy for hepatocellular carcinoma. Issue 10 (8th January 2014) - Takahashi, Shigeo; Kimura, Tomoki; Kenjo, Masahiro; Nishibuchi, Ikuno; Takahashi, Ippei; Takeuchi, Yuki; Doi, Yoshiko; Kaneyasu, Yuko; Murakami, Yuji; Honda, Yoji; Aikata, Hiroshi; Chayama, Kazuaki; et al.
<x xml:space="preserve">Abstract</x> The aim of this study was to evaluate portal vein and bile duct toxicity after stereotactic body radiation therapy (SBRT) for hepatocellular carcinoma (HCC). We retrospectively reviewed 63 patients who were administrated SBRT once for HCC. The prescribed doses were from 48 Gy in four fractions to 60 Gy in eight fractions. Portal vein thrombosis and bile duct stenosis were evaluated. The dose received by 2% of the volume (D2) of the portal vein and bile duct was calculated. Portal vein thrombosis was observed in three patients (4.8%). Common points of these patients were Child–Pugh class B and D2 of the portal vein 40 Gy or more (BED3 ≥200 Gy). Bile duct stenosis was observed in one patient (1.6%). The patient had a history of cholangiocarcinoma and left hepatic lobectomy. Portal vein thrombosis may be necessary to be considered when SBRT for HCC is administrated to patients in higher Child–Pugh class with higher D2 of the portal vein.